PjBL-based Green Chemistry Module: Internalizing Creative and Moral Character in the Context of Wetlands - Sri Rahayu; Suyidno Suyidno; Suryajaya Suryajaya; Fahmi Fahmi (SEJ (Science Education Journal), 2025)
Creative and moral characters developtment is essential in the industrial Era 4.0, but these characters are less integrated in wetland environment-based learning. This study aims to analyze the feasibility of a green chemistry module based on Project-Based Learning (PjBL) to train creative and moral characters in the context of wetlands. This research uses the ADDIE development model. The validation test involved five experts or practitioners, limited trials, and implementation on groups of 15 and 35 students. Data collection utilized module validation instruments, content readability assessments, learning observations, and student responses. The validation results showed that the module had high validity with a score of 90.00. The readability of the module content was very good, with a score of 90.83. Project-based learning can be effectively carried out in limited trials and implementation. Additionally, expressed positive responses regarding of satisfaction, creativity, and moral character. It was concluded that the PjBL-based green chemistry module was feasible for use in training students to develop creative and moral characters in the context of wetlands.